Legal Reformulation of Banking Consumer Protection: Building A Justice-Oriented Regulatory System - Adhan S, Sepriyadi; Yuniati, Ati; Nurfani, Anggun (Faculty of Law, Universitas Pasundan, 2025)
The contractual relationship between banks and customers in credit agreements often places customers in a weak position, as agreements are typically drafted unilaterally by banks and emphasize obligations over rights, creating potential harm. This article aims to reformulate banking customer protection regulations to improve legal certainty and effectiveness. Using a normative legal method with an empirical approach, the research examines the suitability, gaps, and inconsistencies in existing regulations in achieving fair protection. The findings show that consumer protection aligns with Article 28D(1) of the 1945 Constitution, which guarantees the right to legal protection and security. However, current banking regulations lack specific provisions and enforcement mechanisms, resulting in weak protection. Disputes are often resolved through administrative or criminal sanctions that do not ensure fair outcomes. Reform is needed to integrate social protection principles and bridge the gap between legal norms and social realities, ensuring that future regulations promote not only financial efficiency but also fairness and equality in customer relations.